2005
DOI: 10.1038/sj.bjc.6602522
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative stimulation of vascular endothelial growth factor expression by hypoxia and reactive oxygen species: the effect of targeting vascular endothelial growth factor and oxidative stress in an orthotopic xenograft model of bladder carcinoma

Abstract: Elevated thymidine phosphorylase has been shown to correlate with increased angiogenesis and poor prognosis in many cancers including transitional cell carcinoma of the bladder. In vitro studies have demonstrated that thymidine phosphorylase activity causes cellular oxidative stress and increases secretion of vascular endothelial growth factor. In this study, we show that thymidine phosphorylase activity also augments levels of the hypoxia-inducible factor-1a during in vitro hypoxia, and that thymidine phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
(21 reference statements)
1
25
0
Order By: Relevance
“…However, whether protein glycation of AGEs are formed in the cells used in our study, remains to be identified. Brown et al previously reported a possible Schiff base reaction in RT112 cells, and demonstrated the presence of reactive oxygen species by expression levels of the oxidative stress marker heme oxygenase-1 (HO-1) [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether protein glycation of AGEs are formed in the cells used in our study, remains to be identified. Brown et al previously reported a possible Schiff base reaction in RT112 cells, and demonstrated the presence of reactive oxygen species by expression levels of the oxidative stress marker heme oxygenase-1 (HO-1) [31].…”
Section: Discussionmentioning
confidence: 99%
“…It might be, therefore, that TP is preferentially induced by HIF-2a. Of interest is the observation that TP increased the hypoxic expression of HIF-1a in an orthoptic xenograft model of bladder cancer (Brown et al, 2005). This finding suggests that TP can be added to the long list of factors that promote HIF activation.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between TP expression and microvessel density, a histological measure of angiogenesis, has been reported in several solid tumours such as breast (Toi et al, 1995a), ovarian (Reynolds et al, 1994) renal (Imazano et al, 1997), and gastric (Takebayashi et al, 1996). In experimental models, TP overexpression increased tumour cell invasion (Ueda et al, 2001) and tumorigenicity (Griffiths and Stratford 1998;Brown et al, 2005). In man, high tumour expression of TP generally correlates with a poor prognosis in various solid malignancies (Takebayashi et al, 1996;Ikeda et al, 1999) including cervix cancer (Fujimoto et al, 1999;Hata et al, 1999;Ueda et al, 1999).…”
mentioning
confidence: 98%
See 2 more Smart Citations